Manufacturing consent: Italy, the Mutamassirun, Egypt, and the invasion of Libya - Heiss, Andrew (AUC Knowledge Fountain, 2010)
The period between 1902â 12 reveals a number of insights into both Italy's imperial history and Egypt's colonial experience. Facing an economic crisis at home, hundreds of thousands of Italians emigrated to expatriate communities throughout the world, including Egypt. This massive hemorrhage of Italy's population led the government to embrace emigration, and new policies enacted by the Italian foreign ministry after Italy's military failures in Somalia and Eritrea recast migrant Italians as â colonistsâ and global Italian communities as â colonies.â Egypt posed a particularly difficult problem for the foreign ministryâ because of the multi-ethnic character of the Egyptian social system, established by Mohammed Ali and his khedival successors, Europeans benefitted from a number of legal and economic advantages while simultaneously integrating into cosmopolitan Egyptian society as mutamassirun. Emigrant assimilation threatened to destroy Italy's global emigrant colonial model and consequently funded various programs and associations to reinforce notions of italianitÃ . At one level, the bureaucrats and officials in the Cairene and Alexandrian Italian consulates were concerned with the identity of the Italian communities in Egypt, but their strategy was not limited simply to the Italianization of the wayward mutamassirun. Egypt, given its geographic and cultural proximity to the neighboring provinces of Tripolitania and Cyrenaica, represented a strategic backdoor for Italy's program of cultural and economic pÃ©nÃ©tration pacifique into the Mediterranean Basin prior to their military invasion of Libya. Italy sought to manufacture consent for its impending invasion and direct colonization of Libya and engaged in campaigns of propaganda to convince both the Italian community and the Arabic-speaking world that Italy, as a benevolent European nation, was morally justified in colonizing Libya. This thesis uses the archives of the Italian foreign ministry to examine the nature of Italy's campaign to manufacture consent and to ascertain its effectiveness in convincing the Italian mutamassirun and the Egyptian public of its supposedly benign imperial ambitions, and concludes that despite its attempts at promoting Italian imperial benevolence, Italy's hidden colonial ambitions were obvious to the Egyptians and disbelieved by many in the Italian community.